Hubungan Pengetahuan dan Lama Kerja Terhadap Perilaku Hygiene Penjamah Makanan di Instalasi Gizi RSUD Ir. Soekarno Kabupaten Sukoharjo - Dewi Marfuah; Agung Setya Wardana; Rizky Wahyu Astari (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Food sanitation hygiene is an effort to control all physical and biological factors that may cause health problems. Food is in accordance with the standards, so good hygiene and sanitation is needed. The purpose of this study was to determine the relationship between knowledge and length of work on the hygiene behavior of processing workers at the Nutrition Installation of RSUD Ir. Soekarno Sukoharjo. This type of research is analytic observational with a cross sectional approach. The sample of this study were food handlers at the Nutrition Installation of RSUD Ir. Soekarno Sukoharjo as many as 20 people with total sampling technique. Hygiene knowledge was obtained by interviewing using a questionnaire and hygiene behavior was obtained by observing using the behavior observation form. The analysis of the relationship between knowledge and hygiene behavior of food handlers used the Spearman Rank test and the relationship between length of work and hygiene with food handlers used the Chi Square test. The results showed that the relationship between knowledge and hygiene behavior of food handlers obtained a P value = 0.412 and the relationship between length of work and hygiene behavior of food handlers obtained a P value = 0.430. Conclusion There is no relationship between knowledge and length of work with the hygiene behavior of food handlers at the Nutrition Installation of RSUD Ir. Soekarno Sukoharjo.